2009
DOI: 10.1371/journal.pone.0004613
|View full text |Cite
|
Sign up to set email alerts
|

MAGI-1 Modulates AMPA Receptor Synaptic Localization and Behavioral Plasticity in Response to Prior Experience

Abstract: It is well established that the efficacy of synaptic connections can be rapidly modified by neural activity, yet how the environment and prior experience modulate such synaptic and behavioral plasticity is only beginning to be understood. Here we show in C. elegans that the broadly conserved scaffolding molecule MAGI-1 is required for the plasticity observed in a glutamatergic circuit. This mechanosensory circuit mediates reversals in locomotion in response to touch stimulation, and the AMPA-type receptor (AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…They trained L1 larvae with seven blocks (separated by 1 h) of 15 taps at a 60-sec ISI. In contrast to Ebrahimi and Rankin (2007), Emtage et al (2009) found that young adults stimulated in L1 had a decreased TWR magnitude, as measured by the number of quarter body bends executed in the response. This discrepancy may be the result of a different training regime, rearing condition (208C vs. 258C), behavioral measure, or time of training/testing.…”
Section: Long-term Memorymentioning
confidence: 58%
See 3 more Smart Citations
“…They trained L1 larvae with seven blocks (separated by 1 h) of 15 taps at a 60-sec ISI. In contrast to Ebrahimi and Rankin (2007), Emtage et al (2009) found that young adults stimulated in L1 had a decreased TWR magnitude, as measured by the number of quarter body bends executed in the response. This discrepancy may be the result of a different training regime, rearing condition (208C vs. 258C), behavioral measure, or time of training/testing.…”
Section: Long-term Memorymentioning
confidence: 58%
“…This study demonstrates that larval stimulation can affect adult behavior, but the effect depends on the timing and pattern of stimulation. Emtage et al (2009) also studied the effects of early patterned stimulation on adult behavior and identified a gene mediating changes in AMPA receptor localization. They trained L1 larvae with seven blocks (separated by 1 h) of 15 taps at a 60-sec ISI.…”
Section: Long-term Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…SNPs of MAGI2 have been associated with performance in the Wisconsin Sorting Card Test (WCST) in patients with SCZ (Koide et al, 2012), whereas in animal models it was shown to modulate long-term memory and associative learning (Emtage et al, 2009;Stetak et al, 2009). …”
Section: Discussionmentioning
confidence: 99%